Investigator Experiences and Attitudes About Research With Biospecimens. (December 2015) - Rivera, Suzanne M.; Goldenberg, Aaron; Rosenthal, Beth; Aungst, Heide; Maschke, Karen J.; Rothwell, Erin; Anderson, Rebecca A.; Botkin, Jeffrey; Joffe, Steven
To advance scientific knowledge about human diseases and effective therapeutic treatments, investigators need access to human biospecimens and associated data. However, regulatory and procedural requirements may impede investigators' efforts to share biospecimens and data within and across institutions. Although a number of studies have explored experiences and attitudes of study participants and others about biospecimen and data sharing, less is known about investigators' perspectives. We conducted an electronic survey to learn about investigators' experiences and attitudes about research with biospecimens and associated data. A total of 114 practicing scientists from a pool of 60 university medical schools with Clinical and Translational Science Awards (CTSAs) funded by the National Institutes of Health (NIH) participated. We found a high degree of variability in investigators' experiences with institutional review boards (IRBs) when seeking approval to conduct biospecimen research, as well as differences in approaches to informed consent for the collection of specimens. Participants also expressed concerns that the risks of biospecimen research may be overestimated by IRBs. This research suggests that the current regulatory environment for human research protections may require reconsideration with regard to standards for collection, use, and sharing of biospecimens and data.